Intravenous thrombolysis in young adults with ischemic stroke: a cohort study from the international TRISP collaboration - Nybondas, Miranda; Martinez-Majander, Nicolas; Ringleb, Peter A.; Ungerer, Matthias; Gumbinger, Christoph; Trüssel, Simon; Altersberger, Valerian; Scheitz, Jan F; von Rennenberg, Regina; Riegler, Christoph; Cordonnier, Charlotte; Zini, Andrea; et al. (European stroke journal, 2024)
Background and aims: Previous observational data indicate that young adults treated with intravenous thrombolysis (IVT) for acute ischemic stroke have more favorable outcomes and less complications when compared to older adults. Given the limited data on this topic, we aimed to provide more evidence on clinical outcomes and safety in such patients, using a large international thrombolysis registry. - Methods: In this prospective multicenter study, we used data from the Thrombolysis in Ischemic Stroke Patients (TRISP) registry from 1998 to 2020. Patients who received endovascular treatment (EVT), as only treatment or in addition to IVT, were not included in this cohort. Using multivariable regression models, we compared thrombolysed young patients aged 18-49 years with those aged ⩾50 years with regards to the following outcomes: favorable outcome in stroke survivors (modified Rankin Scale ⩽2), symptomatic intracranial hemorrhage (sICH) according to European Cooperative Acute Stroke Study II (ECASS II) criteria, and three-months all-cause death. - Results: Of the 16,651 IVT treated patients, 1346 (8.1%) were 18-49 years. Young adults in TRISP were more often male (59.6% vs 54.0%), had a lower median NIHSS score on admission, 7 (4-13) versus 8 (5-15), and had less cardiovascular risk factors except for smoking (42.0% vs 19.0%) when compared to older patients. When compared to thrombolysed patients aged ⩾50 years, a favorable functional outcome was more likely in young adults: 81.9% versus 56.4%, aOR 2.30 (1.80-2.95), whilst sICH 1.6% versus 4.6%, aOR 0.45 (0.23-0.90) and death 2.3% versus 14.2%, aOR 0.21 (0.11-0.39) were less likely. - Conclusions: Intravenous thrombolysis in young adults is independently associated with higher rates of favorable outcomes and lower rates of complications.
OnlineFirst: 10. Dezember 2024
Gesehen am 11.06.2025